STRATEGIES IN PROMOTING TOURISM PRODUCTS IN PANTAI BIRU, MAKASSAR, INDONESIA - Fatimah Azzahrah (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2025)
The purpose of this study is to analyze promotional strategies that should be applied to tourism products at Pantai Biru, identify the factors that support the increase in tourist visits, and develop recommendations for integrated and sustainable promotional strategies. This research uses a qualitative method with data collected through observation and interviews involving tourism managers, local business actors, and tourists as informants. The findings show that the promotional strategies implemented so far are still limited to the use of simple social media, word-of-mouth promotion, and occasional entertainment events organized at the beach area. The main supporting factors for the increase in tourist visits include the natural beauty of Pantai Biru with its clear seawater, relatively easy accessibility from downtown Makassar, and the involvement of the local community in providing facilities and tourism services. However, the study also found several obstacles in the implementation of promotional activities, including limited funding, lack of innovation in digital content creation, and the absence of an integrated marketing strategy. Based on these findings, this study recommends strengthening the branding of Pantai Biru as a more competitive tourism destination, optimizing the use of digital media with creative and interactive content, and developing multi-stakeholder collaboration that involves local communities, managers, and tourism business actors. In addition, the principle of sustainability needs to be integrated into every promotional activity so that the development of tourism is not only oriented toward increasing the number of visitors but also maintaining the preservation of the coastal environment and improving the welfare of local communities. This research is expected to provide practical contributions for managers and tourism business actors in designing more effective promotional strategies, while also serving as a reference for the development of sustainable tourism in Makassar. In the future, the findings of this study may also serve as a consideration for further research on promotional strategies in other destinations with similar characteristics, so that the results are not only beneficial locally but also relevant in the context of national tourism development. Such strategies will strengthen the long-term competitiveness of Pantai Biru.